Financial management theory and practise - Brigham, Eugene F. (Dryden Press series in finance, 1997)
Continuing the four goals from the first edition, i.e. helping students to make good financial decisions, providing a solid text for the introductory MBA course, motivating students by demonstrating finance is relevant and interesting, and presenting the material clearly, this Tenth Edition promises to be the best yet. Written by a highly-acclaimed, best selling, author team, this text remains the only MBA-level text to present a balance of financial theory and applications.